Penerapan Nilai Budaya Religius dalam Meningkatkan Prestasi Siswa di SD Darul Hikam Bandung - Mubarok, Husni; Nada, Muhammad Yusrun; Silmia, Ami; Fadhila, Nur Laila; Maghfiroh, Rihun Nada; Putri, Evi Rismala (ALSYS, 2022)
This study aims to determine the effect of applying religious cultural values in improving student achievement at SD Darul Hikam Bandung. The results of the research are expected to contribute to the development of the Management of the Application of Religious Cultural Values. This research uses a qualitative approach with a case study type of research. Data collection techniques using the method of observation, interviews, and documentation. While the data analysis technique used the Iles and Huberman model analysis with the following steps: data analysis, data reduction, data presentation, and drawing conclusions or verification. The results of this study indicate that the application of religious cultural values at SD Darul Hikam Bandung can affect the improvement of student achievement, and has an effect on increasing student discipline and awareness in worship, as well as social attitudes and community harmony.